Assessing Groundwater Potential Zones and Their Implications for Landslides in the Upper Wabe-Shebele River Basin of Southeastern Ethiopia - Siraj Beshir; Awdenegest Moges; Mihret Dananto (Journal of Engineering)
Groundwater is an essential resource, and its long-term availability and usability are closely tied to its ability to recharge. Therefore, the objective of this study was to generate a geospatial map of groundwater potential and its implications for landslides in the Upper Wabe-Shebele River Basin. To achieve this, an integrated approach was employed, combining GIS-based MCDM under AHP. The study considered rainfall patterns, land use and land cover, lineaments and drainage density, soil texture, lithology, slope, proximity to roads, and static water level. These influential factors were identified through a combination of desk reviews, expert knowledge, and experience in the field of groundwater potential mapping. Then, a pairwise comparison matrix was formed to assign weights to each factor and their subparameters based on their relative importance to groundwater potential. The final groundwater potential map was generated using the weighted overlay analysis tool in ArcGIS 10.7. By analyzing the groundwater potential map and the incorporated factors, a comprehensive understanding of groundwater resources and their implications for landslide occurrences in the study area was interrelated. The AHP analysis displayed an acceptable positive principal eigenvalue (9.401) and a consistency ratio of 0.035 < 0.1. Groundwater potential zones occupying 1314.73 km2 (12.81%), 4463.06 km2 (43.5%), 3236.23 km2 (31.54%), 283.31 km2 (2.76%), and 961.93 km2 (9.38%) were identified as very good, moderate, poor, and very poor groundwater potential zones, respectively. The accuracy of the groundwater potential map was evaluated by overlaying it with existing borehole data. This comparison revealed a high degree of agreement, with approximately 80% of the data points consistent with the maps. In addition, a positive correlation between the groundwater potential zones and the occurrence of landslides was observed. Based on these findings, sustainable land resource utilization is suggested as an approach to enhance groundwater management and mitigate landslide risks.